Stratifikasi Sosial dalam Budaya A’matoang Masyarakat Turatea Kabupaten Jeneponto - Syarifuddin Syarifuddin (Equilibrium: Jurnal Pendidikan, 2017)
This study aims to describe the culture of A'matoang and the form of social stratification in A'matoang Culture of Turatea people of Jeneponto Regency. Technique of taking informant which used in this research is Purposive sampling based on criterion which have been determined by researcher. Number of informants as many as 15 people aged 25-60 years. Data collection techniques used observation, interview, documentation and participatory methods. The result of the research shows that: (1) A'matoang culture is a series of marriage process, has meaning giving or giving in the form of goods such as clothes, sarong, songkok and veil to mother-in-law to the father-in-law of the men. (2) The form of social stratification in A'matoang cultures of society includes the large number and luxury of pa'matoang which means high social status, whether it is measured from the wealth possessed or from the nobility or karaeng lineage.